Risks Management in Travel Business: Peculiarities, Types Criteria of Estimation - Anatolievna Kiseleva, Irina; Vladimirovich Karmanov, Mikhail; Vladimirovich Korotkov, Anatoly; Ivanovich Kuznetsov, Vladimir; Samuilovich Gasparian, Mikhail; ., . (International Journal of Engineering and Technology, 2018)
The article considers important issues on the security of travel business as a component of the stateâ€™s social and economic system and methods of its impact on risks. The major purpose of this article is to identify the main principles that substantiate the peculiarities of risk assessment in the travel business as the main element contributing to the achievement of travel security, as well as to study instruments and types of risks on the travel services market. The study subject is the security of the travel business. The study object is the market of travel services.The development of tourism technologies is the leading trend of the world economy stipulated by social restructuring of the modern society. The Russian Federation has defined the economic task of the state policy related to travel services. This is to turn tourism into a competitive, innovative, sustainable and highly-profitable sector of the national business. Travel business involves a comprehensive system of relations between suppliers and consumers of the relevant services, between travel agencies and their competitors, as well as among business partners. The operation of a travel agency on the market includes the following: selection of a market niche; development of a travel product; determination of the volume of services provided; improvement of pricing formation; expansion of advertising activities; scientific research; attraction of investments; interaction with other companies, and relations with government bodies. Currently methods and models are intensively implemented in the formation and development of travel management systems, which is associated with the increased competitiveness of the products offered on the travel market.The identification of risks in the operation of a travel company can become a guarantee of its successful and well-coordinated activity. It is possible to quickly and timely identify risks of a travel agency by using the SWOT analysis as a strategic management instrument.Â Â Â